Veronica arguteserrata Reg. et Schmalh. – новий адвентивний вид флори України - МОЙСІЄНКО, ІВАН ІВАНОВИЧ; ЄНА, АНДРІЙ ВАСИЛЬОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Veronica arguteserrata Reg. et Schmalh. – новий адвентивний вид флори України